The organizational climate at Al-Mustansiriya University from the point of view of the teaching staff (Journal of the College of Basic Education, 2022)
The university plays an important basic and social role as a platform for cultural and scientific enlightenment. It seeks to develop society. If we want to talk about the role of the university, we can say in general that its role is to prepare individuals who are able to continue life and work. The university personality of the human being, and because the basis of work in it is the human element represented by the members of the teaching staff and what should be provided to them in terms of an organizational climate that suits the task entrusted to them, so that each one of them can move, innovate and produce without feeling that he is being watched or threatened, which provides spaces It is a freedom that allows teachers to exchange opinions and practice all kinds of activities, whether these activities are social, political or cultural.